2016
DOI: 10.1523/jneurosci.1850-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Mismatch Signals Are Modulated by the Strength of Neural Predictions and Their Similarity to Outcomes

Abstract: The hippocampus is thought to compare predicted events with current perceptual input, generating a mismatch signal when predictions are violated. However, most prior studies have only inferred when predictions occur without measuring them directly. Moreover, an important but unresolved question is whether hippocampal mismatch signals are modulated by the degree to which predictions differ from outcomes. Here, we conducted a human fMRI study in which subjects repeatedly studied various word-picture pairs, learn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 78 publications
4
72
3
Order By: Relevance
“…We chose posterior medial cortex (PMC), a critical region in the recollection network that has been shown to reinstate encoding patterns during retrieval (Bird et al, 2015; Kuhl et al, 2011; Long et al, 2016; Chen et al, 2017) to serve as a control region. Critically, we defined this region from the same contrast as the mPFC ROI.…”
Section: Resultsmentioning
confidence: 99%
“…We chose posterior medial cortex (PMC), a critical region in the recollection network that has been shown to reinstate encoding patterns during retrieval (Bird et al, 2015; Kuhl et al, 2011; Long et al, 2016; Chen et al, 2017) to serve as a control region. Critically, we defined this region from the same contrast as the mPFC ROI.…”
Section: Resultsmentioning
confidence: 99%
“…Such a mechanism, potentially based on the pattern completion processes of the hippocampus (Marr, 1971;Horner, Bisby, Bush, Lin, & Burgess, 2015), appears distinct from the pattern separating mechanisms of the hippocampus (Marr, 1971;McNaughton & Morris, 1987;O'Reilly & McClelland, 1994;Leutgeb, Leutgeb, Moser, & Moser, 2007;Yassa & Stark, 2011). Research on this process has shown that the hippocampus responds to highly similar or overlapping stimuli Bakker, Kirwan, Miller, & Stark, 2008;Duncan, Curtis, & Davachi, 2009;Long, Lee, & Kuhl, 2016) and creates distinct representations of such stimuli, potentially in an effort to minimize interference (Hulbert & Norman, 2015;Favila, Chanales, & Kuhl, 2016;Chanales, Oza, Favila, & Kuhl, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, what are the boundary conditions that determine when representations of overlapping memories are integrated rather than separated, and how might we manipulate the formation of integrated codes of experience? While initial findings suggest that the strength of existing knowledge [18], the degree of memory reactivation during encoding [17], the magnitude of memory-based prediction errors [15], and task demands [84] all impact the likelihood of integration, more work is needed to understand the full complement of conditions that influence how we represent related episodes in memory. As noted above, different memory circuits (e.g., anterior and posterior hippocampus) may integrate information at different scales.…”
Section: Discussionmentioning
confidence: 99%
“…Medial PFC, which is thought to represent mental models that guide behavior [13, 14], may further bias hippocampal pattern completion to the most relevant prior knowledge [9]. Hippocampus then signals deviations between current events and reactivated memories, triggering memory updating [1, 15, 16]. Finally, new content is integrated with existing mental models via hippocampus—mPFC interactions [1719].…”
Section: Introductionmentioning
confidence: 99%